Evaluating the resilience of a full-scale down-flow hanging sponge reactor to shock-loadings. Issue 1 (2nd December 2021) - Onodera, Takashi; Okubo, Tsutomu; Takayama, Daisuke; Syutsubo, Kazuaki; Yamaguchi, Takashi; Uemura, Shigeki; Ohashi, Akiyoshi; Harada, Hideki
Abstract: The effect of shock-loading on the performance of a full-scale down-flow hanging sponge (DHS), used to treat effluent from an up-flow anaerobic sludge blanket treating municipal sewage, was evaluated. This full-scale DHS reactor comprises a polyurethane sponge that retains the sludge. It has a capacity of 500 m 3 /day and, at the time of this study, had been operating at a sewage treatment plant in India for more than 1, 300 days. The DHS reactor was exposed to shock loadings of organics at double the normal rate for 400 min under summer and winter conditions. The results showed that the DHS reactor maintained stable operation under the organic shock loading and that it returned to a steady state soon after restart, confirming that the reactor was resilient to organic shock loadings. HIGHLIGHTS: A full-scale down-flow hanging sponge reactor was evaluated in India. The DHS reactor was exposed to double organic rate for 400 min. The DHS reactor produced stable effluent quality under shock loadings. The DHS achieved a steady state soon after shock loadings under summer and winter. The full-scale experiment verify that the DHS was resilient to shock-loadings. Graphical Abstract